دبلوماسية المساعدات الإنسانية: المفاهيم ومجالات التطبيق: (Humanitarian Aid Diplomacy: Concepts and Areas of Application) - Al-Thabeti, Muhammad Abdul Mohsen; Mahyoub Murshed, Dr. Amer Abdulwahab; Abdul Rahman, Mohamad Zaidi (Online Journal of Research in Islamic Studies, 2025)
ملخص: شهد القرن العشرون وبداية القرن الحادي والعشرين زيادة ملحوظة في عدد الحروب والنزاعات المسلحة، مما أبرز أهمية تنشيط دبلوماسية المساعدات الإنسانية لتخفيف آثار الأزمات وتعزيز المساعدات الإنسانية، حيث يقصد بالمساعدات الإنسانية " مساعدة وإجراءات مصممة لإنقاذ الأرواح وتخفيف المعاناة والحفاظ على الكرامة الإنسانية وحمايتها أثناء حالات الطوارئ وفي أعقابها"، ومن ثم، فإن العمل الإنساني يُفهم على أنه واجب عالمي يرتكز على مبدأ الإنسانية المشتركة. ويمكن أن يستلزم توفير المساعدة والحماية لأولئك الذين يعانون في الكوارث الطبيعية وحالات الطوارئ المعقدة والتي من صنع الإنسان. وعليه يهدف هذا البحث إلى تعريف القارئ بالمفاهيم الأساسية المتعلقة بدبلوماسية المساعدات الإنسانية، وتوضيح أبرز مجالات استعمالها، فضلاً عن تحليل التحديات التي تواجهها في السياقات الحالية. تُطرح في هذه الدراسة إشكالية تتعلق بالسؤال: ما هي المفاهيم الأساسية المرتبطة بدبلوماسية المساعدات الإنسانية؟ وما هي أبرز مجالات تطبيقها في ظل تزايد الأزمات الإنسانية؟اعتمدت الدراسة على المنهج الوصفي التحليلي، واستندت إلى مجموعة من الأدبيات والدراسات المعاصرة. وقد أسفرت النتائج عن أن دبلوماسية المساعدات الإنسانية تعتبر ممارسة قديمة، إلا أن استخدامها كمفهوم في الأوساط الأكاديمية يعد حديثًا نسبيًا. كما أظهرت الدراسة أن إنشاء اللجنة الدولية للصليب الأحمر في عام 1863 يمثل نقطة تحول هامة في تاريخ العمل الإنساني المنظم. من بين مجالات التطبيق الهامة التي ناقشها البحث: حالات الطوارئ المعقدة، الأوبئة، المجاعات، والحروب الأهلية، مع التركيز على صعوبة الوصول إلى الرعاية الصحية في المناطق المتضررة.أوصت الدراسة بضرورة إجراء أبحاث معمقة حول دبلوماسية المساعدات الإنسانية من منظور إسلامي، خاصةً أن الإسلام قدم اهتمامًا كبيرًا للبعد الإنساني في أوقات الحروب والنزاعات، مما يستدعي تعزيز هذا المجال من خلال مقاربة تحليلية وسياقية تتماشى مع الواقع المعاصر. الكلمات المفتاحية: الدبلوماسية، المساعدات الإنسانية، الحروب، الكوارث الطبيعية، القانون الدولي الإنساني. ABSTRACT In the past few decades, there has been a notable rise in wars and armed conflicts around the globe, underscoring the pressing necessity for effective humanitarian aid diplomacy to address crises and alleviate human suffering. This research intends to examine the fundamental ideas associated with humanitarian aid diplomacy, pinpoint its main applications, and evaluate the significant obstacles it encounters in the current global landscape. The primary research question seeks to answer: What are the essential ideas behind humanitarian aid diplomacy? Which areas see its most frequent use? This investigation employs a descriptive and analytical methodology, drawing on a review of pertinent literature and case studies. The results indicate that although humanitarian diplomacy has been practiced for a long time, it has only recently attracted substantial attention in academic discussions. The establishment of the International Committee of the Red Cross in 1863 represented a pivotal moment for organized humanitarian initiatives. Humanitarian diplomacy is particularly vital in addressing issues like complex emergencies, civil conflicts, outbreaks of disease, famines, and inadequate healthcare access in war-torn areas. Furthermore, the study encourages more research into humanitarian aid diplomacy from an Islamic viewpoint, as Islamic principles strongly value humanitarianism, particularly during conflict and emergencies. This perspective could provide important insights and contributions to the global conversation on humanitarian efforts. Keywords: Diplomacy, Humanitarian Aid, Armed Conflicts, Natural Disasters, International Humanitarian Law.